2021
DOI: 10.1177/17448069211021698
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcium-stimulated adenylyl cyclase subtype 1 (AC1) for the treatment of neuropathic and inflammatory pain in adult female mice

Abstract: Cortical long-term potentiation (LTP) serves as a cellular model for chronic pain. As an important subtype of adenylyl cyclases (ACs), adenylyl cyclase subtype 1 (AC1) is critical for the induction of cortical LTP in the anterior cingulate cortex (ACC). Genetic deletion of AC1 or pharmacological inhibition of AC1 blocked behavioral allodynia in animal models of neuropathic and inflammatory pain. Our previous experiments have identified a lead candidate AC1 inhibitor, NB001, which is highly selective for AC1 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…Previous studies have shown that intraperitoneal, intracerebral injection, or peroral administration of NB001 reduces pain-related behavioral responses in rodents with neuropathic or inflammatory pain. 17 , 34 , 35 In our present study, peroral administration of NB001 in chickens also significantly reduced spontaneous pain behaviors and mechanical hypersensitivity in gouty pain chickens. These data show that the peroral administration of NB001 has a good therapeutic effect on gouty pain.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies have shown that intraperitoneal, intracerebral injection, or peroral administration of NB001 reduces pain-related behavioral responses in rodents with neuropathic or inflammatory pain. 17 , 34 , 35 In our present study, peroral administration of NB001 in chickens also significantly reduced spontaneous pain behaviors and mechanical hypersensitivity in gouty pain chickens. These data show that the peroral administration of NB001 has a good therapeutic effect on gouty pain.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, we also found that NB001 had an analgesic effect on both male and female chickens, which is consistent with our one recent study in that we found NB001 showed an analgesic effect in female mice. 35 …”
Section: Discussionmentioning
confidence: 99%
“…As a novel target for chronic pain, adenylyl cyclase 1 (AC1) is essential for the presynaptic enhancement of glutamate release and the postsynaptic potentiation [ 12 , 41 ]. Moreover, the AC1 inhibitor, NB001, produces powerful analgesic effects in different animal models of chronic pain [ 21 , 42 ]. Our current findings strongly suggest that the AC1 inhibitor NB001 maybe used for the future treatment of chronic pain in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Activity time, standing time and hanging time were recorded and analyzed. During 24 h recording, mice were housed in standard cages on a 12 h light/dark cycle with food and water provided ad libitum [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In line with this neuron-specific expression, these ACs play specialized roles in synaptic plasticity in the spinal cord and brain of rodents ( Wang et al, 2011 , Griggs et al, 2019 ) where they augment NMDAR currents upstream of PKA phosphorylation of these channels ( Liauw et al, 2005 , Wang and Zhang, 2012 ). Genetic knockout of AC1 in mice demonstrates an important role for the Adcy1 gene in chronic hypernociception that occurs after nerve injury or other injuries ( Vadakkan et al, 2006 , Xu et al, 2008 , Wang et al, 2011 , Corder et al, 2013 , Griggs et al, 2019 , Zhou et al, 2021 ). Genetic knockout of Adcy8 suggests a specialized role for this enzyme in anxiety-like behavior in mice ( Bernabucci and Zhuo, 2016 ) but does not support a role in mechanical hypersensitivity after inflammation, although formalin nocifensive behavioral responses are attenuated in mice lacking the Adcy8 gene ( Wei et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%